Diabetogenic T cells recognize insulin bound to IA(g7) in an unexpected, weakly binding register - Stadinski, Brian D. (National Academy of Sciences, 2010)
A peptide derived from the insulin B chain contains a major epitope for diabetogenic CD4(+) T cells in the NOD mouse model of type 1 diabetes (T1D). This peptide can fill the binding groove of the NOD MHCII molecule, IA(g7), in a number of ways or “registers.” We show here that a diverse set of NOD anti-insulin T cells all recognize this peptide bound in the same register. Surprisingly, this register results in the poorest binding of peptide to IA(g7). The poor binding is due to an incompatibility between the p9 amino acid of the peptide and the unique IA(g7) p9 pocket polymorphisms that are strongly associated with susceptibility to T1D. Our findings suggest that the association of autoimmunity with particular MHCII alleles may be do to poorer, rather than more favorable, binding of the critical self-epitopes, allowing T-cell escape from thymic deletion.